Overview of the Germline and Expressed Repertoires of the TRB Genes in Sus scrofa - Massari, Serafina; Bellini, Mariagrazia; Ciccarese, Salvatrice; Antonacci, Rachele (Frontiers in Immunology, 2018)
The α/β T cell receptor (TR) is a complex heterodimer that recognizes antigenic peptides and binds to major histocompatibility complex (MH) molecules. Both α and β chains are encoded by different genes localized on two distinct chromosomal loci: TRA and TRB. The present study employed the recent release of the swine genome assembly to define the genomic organization of the TRB locus. According to the sequencing data, the pig TRB locus spans approximately 400 kb of genomic DNA and consists of 38 TRBV genes belonging to 24 subgroups located upstream of three in tandem TRBD-J-C clusters, which are followed by a TRBV gene in an inverted transcriptional orientation. Comparative analysis confirms that the general organization of the TRB locus is similar among mammalian species, but the number of germline TRBV genes varies greatly even between species belonging to the same order, determining the diversity and specificity of the immune response. However, sequence analysis of the TRB locus also suggests the presence of blocks of conserved homology in the genomic region across mammals. Furthermore, by analysing a public cDNA collection, we identified the usage pattern of the TRBV, TRBD and TRBJ genes in the adult pig TRB repertoire, and we noted that the expressed TRBV repertoire seems to be broader and more diverse than the germline repertoire, in line with the presence of a high level of TRBV gene polymorphisms. Because the nucleotide differences seems to be principally concentrated in the CDR2 region, it is reasonable to presume that most T cell β-chain diversity can be related to polymorphisms in pig MH molecules. Domestic pigs represent a valuable animal model as they are even more anatomically, genetically and physiologically similar to humans than are mice. Therefore, present knowledge on the genomic organization of the pig TRB locus allows the collection of increased information on the basic aspects of the porcine immune system and contributes to filling the gaps left by rodent models.